Penerapan Hukum Pidana Positif Terhadap Kebiasaan Masyarakat Yang Dianggap Sebagai Tindak Pidana Perjudian Di Wilayah Pekanbaru - Sridefi Sinaga; Erdianto '; Dessy Artina (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2017)
Criminal law is the governing law of the violations and crimes against the public interest. Where the act which is punishable by a suffering or torture. The criminal law is not a law containing new norms, but merely regulates violations and crimes against the norms of law regarding the public interest. Public order and security will be maintained when every member of society to obey the rules and norms that exist in that society. The local community culture thrive in a community environment and experience the social changes and cultural place in society. Many cultures were initially regarded as indigenous traditions of a region, but as the development of the times turns into a habit of breaking the law. Examples habits of the people who constitute the crime of gambling among others that when there is a mother who has given birth then there will be some adults who take care of the mother throughout the night, to fill the time the guards would usually play cards that use betting money or anything else that has value , In Chinese society there is also a habit when somebody dies there will be those who guard people who died while playing cards or other games that use money bets. Legally of course this practice the elements of gambling, as in article 303 Criminal Code.Purpose of this paper is the first, How does the application of the criminal law of the habitual positive people who are considered as a crime of gambling in the territory of Pekanbaru. Second What are the obstacles in the application of the criminal law of the habitual positive people who are considered as criminal acts in the area of Pekanbaru. Third, How to overcome obstacles in the implementation of positive criminal law against the habits of the people who considered a criminal offense of gambling in the territory of Pekanbaru.The results of research and discussion is the first, In the implementation mechanism of the application of positive criminal law against social custom which is regarded as a criminal act of gambling are often not enforced by the police. Gambling committed while in traditional events considered breaking the law despite the elements in articles 303 and 303 bis Book of Law Criminal Law is clear, but because it was already in the tradition then carried out the arrest because it was violating the limits customary in society. Second, some aspects of the constraints in the implementation of positive criminal law against the habits of the people who considered a criminal offense, those barriers are: Law enforcement officers in this case represented by the police is an important component in law enforcement criminal act of gambling is considered as an act criminal gambling but in fact when it found the criminal case gambling is considered a criminal offense gambling had sometimes felt unable to make an arrest or the arrest of persons who commit such offenses even though the elements are obvious, but because it is considered a customary ritual or event locals then police officers did not follow it strictly. Local communities' awareness it is also very low. Even as interviewed by the author, namely when there is a specific event and there is a gambling game, the community will be happy and willing to follow the event. There should be a legal awareness of the local community. Legal awareness as adherence to the law, is within the law, in accordance with legal regulations realized or understood. When the community is aware of the law they will obey existing laws and might be able to replace gambling with other things more positive.Keywords : Aplication - Positif Law – Gambling Habits